1997
DOI: 10.1177/014920639702300305
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Complexity and Development of the leaderplex Model

Abstract: Researchers have considered cognitive, social, and behavioral aspects of leadership, but except for Zaccaro (1996a, 1996b), not all three simultaneously. A comprehensive treatment of all three aspects in one model enhances the understanding of leadership. We review research in the areas of cognitive, social, and behavioral complexity and propose an integrative framework—the Leaderplex Model. We set forth propositions to stimulate integrative, empirical leadership research in such areas as diversity, global org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
124
0
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(134 citation statements)
references
References 76 publications
4
124
0
6
Order By: Relevance
“…Consistent with previous research on expertise (Glaser &Chi, 1988;Shanteau, 1992) and leadership (Day & Lance, 2004;Hooijberg et al, 1997;Lord & Hall, 2006;, experienced leaders identified significantly more elements or dimensions of the scenario than did novice-level cadets. With respect to specific categories of dimensions, experienced leaders identified a greater number of tactical concerns than cadets, as well as a greater number of concerns about managing relationships and managing the self.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Consistent with previous research on expertise (Glaser &Chi, 1988;Shanteau, 1992) and leadership (Day & Lance, 2004;Hooijberg et al, 1997;Lord & Hall, 2006;, experienced leaders identified significantly more elements or dimensions of the scenario than did novice-level cadets. With respect to specific categories of dimensions, experienced leaders identified a greater number of tactical concerns than cadets, as well as a greater number of concerns about managing relationships and managing the self.…”
Section: Discussionsupporting
confidence: 85%
“…Effective leadership can be viewed, therefore, as a form of expertise that includes both a broad response repertoire and the ability to apply this knowledge to the resolution of everyday problems (Day & Lance, 2004). Such findings are consistent with the assumptions of the Leaderplex model of leadership growth and effectiveness (Hooijberg, Hunt, & Dodge, 1997), which views social and cognitive complexity as major determinants of behavioral complexity and leadership effectiveness (Denison, Hooijberg, & Quinnl, 1995). Increased cognitive complexity is defined in terms of the two complementary processes of differentiation, referring to the number of dimensions or concepts used in the perception of the social or physical environment, and integration, which represents the degree to which individual dimensions can be combined to meet the demands of specific situations (Day & Lance, 2004;Hooijberg et al, 1997).…”
Section: Experience and Leadershipsupporting
confidence: 87%
See 2 more Smart Citations
“…Management of tension and complexity, which are endemic in organizational settings, and crucial in building ambidextrous organizations, requires that managers respond to various roles (Hooijberg, Hunt, & Dodge, 1997;Lawrence, Lenk, & Quinn, 2009), equilibrate opposing forces (Lewis, 2000) and tackle conflicting demands (Chang, 2015) by displaying appropriate and diverse modes of influence. Specifically, managers must be capable of promoting both creativity and discipline (Wang & Rafiq, 2014), by allowing experimentation, while at the same time enforcing tight control (Turner & Lee-Kelley, 2012), contradictions that have been found to be synergistic in achieving organizational ambidexterity (Andriopoulos & Lewis, 2009).…”
mentioning
confidence: 99%